Clinical applications of evidence-based family interventions - Corcoran, Jacqueline (Oxford : Oxford University Press, 2003)
Mental health service delivery systems are increasingly moving toward empirically-validated approaches, and practitioners need guidelines as to how such treatments may be implemented in daily practice. This text reviews treatments that are relevant for family practice in the social work setting.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Family social work; Family psychotherapy